Pengaruh Model Pembelajaran Joyful Learning Terhadap Minat Belajar Siswa Di MTsN 3 Surabaya - Aulia Hanani; Yuliastutik (Universitas Sains dan Teknologi Komputer, 2023)
Teacher creativity in carrying out learning activities is an important thing to increase students' interest in learning. Teaching creativity can be in the form of using fun learning models. In this case, fun learning is not only to make it easier for students to understand the material presented, but to help students in increasing their interest in learning so that they can get maximum learning results. The purpose of this research is to determine whether there is an influence of fun learning models on student learning interests. This study uses a quantitative research approach with a descriptive type of research using data collection techniques in the form of documentation and questionnaires. While the data that has been obtained is analyzed using pearson product moment with the help of the Statistical Package for the Social Sciences application. The results showed that: (1) the implementation of the joyful learning learning model in MTsN 3 can be categorized as